Brief Reports - Survival after Sublobar Resection for Early-Stage Lung Cancer: Methodological Obstacles in Comparing the Efficacy to Lobectomy. Issue 3 (March 2016) - Taioli, Emanuela; Yip, Rowena; Olkin, Ingram; Wolf, Andrea; Nicastri, Daniel; Henschke, Claudia; Yankelevitz, David; Pass, Harvey; Flores, Raja M.
ABSTRACT : Introduction: : Surgery is the treatment of choice for early‐stage lung cancer (LC). Although lobectomy (L) is the historic standard treatment, the issue of whether long‐term outcomes of sublobar resection (SL) are comparable is still under debate. The objective of this study was to perform a review of the literature on 5‐year survival rates after SL compared to L for patients with early‐stage LC. Methods: : A priori inclusion criteria were as follows: (1) observational studies, (2) L compared to SL for early‐stage LC, (3) radiographic staging by computed tomography scan, and (4) 5‐year survival reported. A Medline search through January 2015 resulted in 31 studies representing 23 distinct datasets. The absolute difference in 5‐year survival was calculated and plotted for each study. Results: : L was performed in 4564 patients and SL in 2287 patients. Of 19 studies reporting the reason for SL, 11 indicated that SL was performed because of comorbidities or impaired cardiopulmonary function. Four studies showed no difference in 5‐year survival, 13 favored L, and six favored SL. One propensity score study favored L and the other favored SL. Of 20 studies reporting recurrence rate, 11 favored L and nine favored SL. Conclusions: : Studies comparing 5‐year survival rates of SL to L are sufficiently heterogeneous to prevent carrying out traditional meta‐analysis. SL survival is often similar to L when adjustments are made for age, comorbidities, or impaired cardiopulmonary function. New approaches are needed for the comparison of L to SL.